2017
DOI: 10.1177/0972150917692063
|View full text |Cite
|
Sign up to set email alerts
|

SME Managers and Financial Literacy

Abstract: The aim of this study is to examine the level of small and medium enterprises (SMEs) business owners–managers’ financial literacy and its impact on firm’s performance. The article applied a random sample and structural equation modelling (SEM) approaches in assessing the influence of SME business owners–managers’ level of financial literacy within the three states in the southwest Nigeria. The findings show the complete effect of business owner–manager’s financial knowledge, financial awareness and financial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 62 publications
7
103
1
5
Order By: Relevance
“…The positive influence of financial literacy on sustainability is consistent with the results of Eniola and Entebang [20], who found that financial literacy had a direct, positive impact on the performance of Nigerian SMEs, and Purnomo [109], who also found that financial literacy had a direct impact on SMEs' performance. We identified financial literacy as an important component of organisations' intellectual capital and thus our findings are consistent with those of Carmeli and Tishler [31], who found that intellectual capital had a positive effect on SMEs' sustainability.…”
Section: Discussion Of the Findingssupporting
confidence: 87%
See 2 more Smart Citations
“…The positive influence of financial literacy on sustainability is consistent with the results of Eniola and Entebang [20], who found that financial literacy had a direct, positive impact on the performance of Nigerian SMEs, and Purnomo [109], who also found that financial literacy had a direct impact on SMEs' performance. We identified financial literacy as an important component of organisations' intellectual capital and thus our findings are consistent with those of Carmeli and Tishler [31], who found that intellectual capital had a positive effect on SMEs' sustainability.…”
Section: Discussion Of the Findingssupporting
confidence: 87%
“…Empirical studies have shown that levels of financial literacy are low amongst entrepreneurs. Eniola and Entebang [20] identified a lack of financial literacy as a common problem in SMEs; lack of financial literacy has an impact on business organizations in the starting up phase and subsequently. Kotzè and Smit [21] concluded that lack of financial literacy was the main reason for the failure of SMEs.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the last decade there have been many studies conducted by previous research regarding financial literacy, especially in emerging countries, such as India [6], Bosnia and Herzegovina [7], South Africa [8][9][10][11], Latvia [12], Dominican Republic [13], Mexico [14], Tanzania [15], and Nigeria [16]. Most of studies regarding financial literacy in emerging countries focused on knowledge standards of financial literacy, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, insufficient financial literacy has been recognised as one of the main reasons for the failure of SMEs [10] and as a barrier to the sustainable development for these companies [7]. [11] identified the impact of the lack of finance on business organisations in the start-up period. The role of knowledge-based resources in promoting sustainability in SMEs is a very contemporary issue and financial literacy has been considered as the key to financial decision making [7].…”
Section: Introductionmentioning
confidence: 99%